Searching for a cross-cultural definition of suffering; a bibliographic review - Rafael Montoya Juárez; Jacqueline Schmidt Río-Valle; Diego Prados Peña (Universidad de Alicante, 2012)
Introduction: Could we offer a definition of suffering free from our own subjectivity? The aim of the current bibliographic review is to offer a definition of suffering, leaving its measurement aside as a secondary matter. Methods: Medline, Proquest and Scopus databases in English were reviewed and 30 articles were selected. Results: Most authors support the complementarity of pain/symptom and suffering. The definition offered by E. Cassell is the most broadly cited in the literature: "Severe stress state associated with threatening events for personal integrity. The suffering of a person is conditioned by society and culture. There are three types of strategies in order to detect and/or measure suffering: Clinical practice, qualitative and quantitative research. Discussion: It is necessary to go deeper in the concept of suffering in order to find a cross - cultural definition which takes into account individual and socio - cultural aspects. Instruments for the objective measure of the intensity of suffering have not been found. Suffering is a subjective experience.